ANALISA KUALITAS WEB EMPLOYEE SELF SERVICE (ESS) PADA PT. PLN UIPJBB MENGGUNAKAN METODE WEBQUAL 4.0 DAN IPA - Heru Susanto; Suparni Suparni; Lilyani Asri Utami (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2020)
PT PLN (Persero) West Java Development Main Unit (UIPJBB) has used an information system to make it easier for employees to access information and personnel activities such as attendance, leave, CV, information on the stages of requesting an Official Travel Letter (SPPD), and other related information. with staffing by using a web called Employee Self Service (ESS). The quality of ESS web services has never been measured based on user perceptions and levels of importance or expectations. This study intends to analyze the quality of the ESS web using WebQual 4.0 as a questionnaire consisting of three dimensions in the form of Usability, Information Quality, and Service Interaction dimensions, as well as using the IPA method to analyze the level of conformity, compliance (GAP), and quadrants. The results of the level of conformity obtained from 22 statements were still below 100%. The test result statistic shows Asymp.Sig. (2-tailed) worth 0,000 means that there is a gap between Importance and Performance on the ESS website of PT PLN (Persero) UIPJBB. The average of the overall level of conformity is obtained 93.53%, which means that the performance on the web ESS is still below Importance and users are still not satisfied. While the results of GAP analysis are -0.262 <0, then the quality of performance is still lacking and cannot meet the interests of users.